CAPACITY OF GROUP A (TYPE M12) STREPTOCOCCI TO BIND IMMUNE COMPLEXES AND THEIR ROLE IN PATHOGENESIS OF POST-STREPTOCOCCAL GLOMERULONEPHRITIS - L. A. Burova; E. A. Gavrilova; P. V. Pigarevsky; V. G. Seliverstova; V. A. Nagornev; V. A. Schalen; A. Totolian Artem (Медицинская иммунология, 2014)
Abstract. In former studies, using an experimental rabbit model of acute post-streptococcal glomerulonephritis (GAS), we have proven a role of M-like Fc-binding streptococcal proteins (IgG FcBPs) for initiating destructive/degenerative lesions of renal glomeruli that are characteristic to membranous/proliferative and destructive glomerulonephritis. This activity was shown for the strains of types 1, 22 and 49. Their clinical isolates are able to bind Fc fragment of human and rabbit IgG, and are considered as an etiological agent of glomerulonephritis. It is well known that GAS strains of M12 serotype (commonly nephritogenic) are not able to interact with IgG monomers, and usually bind aggregated IgG, in spite of participation of IgG FcBPs in the both events.In present study, the GAS reference strain M12(1800) and twenty-one clinical strains of M12 type isolated from the patients with acute poststreptococcal glomerulonephritis (APSGN) were tested for binding with two artificial immune complexes (ICs): (i) peroxidase – antiperoxidase rabbit IgG (PAP) and (ii) tetanus toxoid – anti-tetanus human IgG (TAT). Streptococcal strain M12 (1800), as well as the majority of clinical isolates (19 strains) were strongly positive for the binding of both ICs tested. Using previously described model of experimental streptococcal glomerulonephritis rabbits were injected with heat-killed M12(1800) and each of two clinical isolates M12(257) and M12(305), positive and negative for the binding of ICs, respectively. Renal tissue material of rabbits injected with M12(1800) and M12(257), but not M12(305), showed strong inflammatory and degenerative changes compatible with pattern observed in APSGN. Streptococcal strains M12(1800) and M12(257), in contrast to strain M12(305), induced circulating anti-IgG, tissue deposition of IgG and C3 as well as secretion of IL-1β, Il-6 and TNF-α by the glomerular mesangial and endothelial cells. Our experimental data suggest that the IC-binding ability of type M12 streptococci should be of importance for the nephritogenic potential of these GAS serotype strains.